Efektivitas Metode Diskusi Kelompok dengan dan Tanpa Fasilitator pada Peningkatan Pengetahuan, Sikap dan Motivasi Remaja Tentang Perilaku Seks Pranikah - Sri Handayani, Ova Emilia, Budi Wahyuni (Berita Kedokteran Masyarakat (BKM), 2009)
Background: The survey result of Indonesian Family Planning Association (PKBI) mentioned that teenagers were started to have sexual relationship when they were 13-18 years old, 60% out of them did not use the contraception, and 85% did that at their own house. This condition showed that pre marital sexual behavior in teenager was very high. Lack of education regarding reproductive health and inappropriate information could caused teenagers having free sexual behavior. This was supported the importance of reproductive health education as preventive action of pre marital sexual behavior for teenager.Objective: This research was aimed to find out group discussion method with or without facilitator that could be more effective in improving knowledge, attitude and motivation of teenager regarding pre marital sexual behavior.Method: This was a quasi experimental research that used pretest-posttest control group design. The sample was selected with purposive sampling technique based on respondent’s characteristic. In addition, the data was analysed with  analysis of variance  (ANOVA).Result:  Knowledge, attitude and motivation of teenager regarding pre marital sexual behavior before the treatment was not significant, knowledge (p = 0,940), attitude (p = 0,357) and motivation (p = 0,260). After the treatment, there was a significant improvement on knowledge (p = 0,00), attitude (p= 0,00) and motivation (p=0,024). The result of ANOVA test showed that there was a significant difference between group discussion with facilitator and group discussion without facilitator in improving teenager’s knowledge (p = 0,018) . While for improvement of attitude and motivation of teenager, there was a significant improvement between group discussion with facilitator and group discussion without facilitator with value of attitude (p= 0,734) and motivation (p= 0,647).Conclusion: Group discussion method with facilitator was more effective in improving knowledge, attitude, and motivation of teenager toward pre marital sexual behavior compare with group discussion method without facilitator.Keywords: reproductive health education, group discussion method, teenager, pre marital sexual behavior,knowledge, attitude, motivation